The Salmon in Pregnancy Study: study design, subject characteristics, maternal fish and marine n-3 fatty acid intake, and marine n-3 fatty acid status in maternal and umbilical cord blood - Miles, Elizabeth A; Noakes, Paul S; Kremmyda, Lefkothea-Stella; Vlachava, Maria; Diaper, Norma D; Rosenlund, Grethe; Urwin, Heidi; Yaqoob, Parveen; Rossary, Adrien; Farges, Marie-Chantal; Vasson, Marie-Paule; Liaset, Bjørn; et al. (The American journal of clinical nutrition, 2011)
Oily fish provides marine n-3 (omega-3) fatty acids that are considered to be important in the growth, development, and health of the fetus and newborn infant. The objectives were to increase salmon consumption among pregnant women and to determine the effect on maternal and umbilical cord plasma marine n-3 fatty acid content. Women (n = 123) with low habitual consumption of oily fish were randomly assigned to continue their habitual diet or were provided with 2 portions of farmed salmon/wk to include in their diet from week 20 of pregnancy until delivery. Median weekly consumption frequency of study salmon in the salmon group was 1.94 portions, and total fish consumption frequency was 2.11 portions/wk in the salmon group and 0.47 portions/wk in the control group (P < 0.001). Intakes of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) from the diet, from seafood, and from oily fish were higher in the salmon group (all P < 0.001). Percentages of EPA and DHA in plasma phosphatidylcholine decreased during pregnancy in the control group (P for trend = 0.029 and 0.008, respectively), whereas they increased in the salmon group (P for trend for both < 0.001). EPA and DHA percentages were higher in maternal plasma phosphatidylcholine at weeks 34 and 38 of pregnancy and in umbilical cord plasma phosphatidylcholine in the salmon group (P < 0.001 for all). If pregnant women, who do not regularly eat oily fish, eat 2 portions of salmon/wk, they will increase their intake of EPA and DHA, achieving the recommended minimum intake; and they will increase their and their fetus' status of EPA and DHA. This trial was registered at clinicaltrials.gov as NCT00801502.